Investigation of internet of things handover process for information centric networking and proxy mobile internet protocol - Mohd Aman, Azana Hafizah; Hassan, Rosilah; Hassan Abdalla Hashim, Aisha; Mohd Ramli, Huda Adibah (Mehran University of Engineering and Technology, 2019)
IoT (Internet of Things) technically connects billions of entities to the Internet. The IoT is divided between the technology and the service itself. As a result, great efforts are needed to join data from many contexts and services. This reason has motivated proposals to develop solutions that can overcome existing issues of limitations for mobility, security, reliability and scalability of IoT. These billions of devices are interconnected to each other either using unicast, multicast or broadcast communications, and mixture of static and mobile communications. This paper aims to investigate the parameters of mobility performance in handover process for mobile multicast IoT environment. Investigation is done quantitatively by evaluating the parameters of handover process for IoT in two networking protocols that are possible to support acceptable mobility performance for IoT. The protocols are ICN (Information Centric Networking) and Proxy Mobile Internet Protocol. The evaluation parameters include packet loss and service recovery time. The metrics are extracted from the handover process flow for each network protocol topology. The service recovery time parameter is assumed as the time duration for each message to travel from sender to receiver, while packet loss parameter depends on the packet arrival rate and service recovery time. The results show that the ICN performs better than Proxy Mobile Internet Protocol. Key Words: Handover, Information Centric Networking, Proxy Mobile Internet Protocol, Packet Loss, Service Recovery Time.